Immunoreactivity of chemically cross-linked gluten and hydrolysates of wheat flour - Majak, Iwona; Leszczyńska, Joanna; Łącka, Agnieszka (Wydawnictwo Politechniki Łódzkiej, 2011)
The immunoreactivity of gluten and wheat flour proteins crosslinked with chosen chemical reagents was investigated. Native proteins and flour hydrolysates subject to enzymatic proteolysis with collagenase and subtilisin were studied. Determination of immunoreactivity was performed with noncompetitive ELISA method with coeliac patients' sera. The lowest immunoreactivity values were obtained during cross-linking of wheat flour hydrolyzates with polyethyleneimine, below 5% of the values for nonmodified flour.